2009
DOI: 10.1038/npp.2009.176
|View full text |Cite
|
Sign up to set email alerts
|

Pimavanserin, a Serotonin2A Receptor Inverse Agonist, for the Treatment of Parkinson's Disease Psychosis

Abstract: Psychotic symptoms occur in up to 40% of patients with Parkinson's disease (PD). Clozapine and quetiapine, two atypical antipsychotic drugs, at doses markedly lower than those effective in schizophrenia, which, nevertheless, still cause sedation, hypotension, and other side effects, are widely used to treat psychotic symptoms in patients with PD psychosis (PDP), although quetiapine has never been shown to be effective in a placebo-controlled study. The demonstrated efficacy of clozapine in PDP has been attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
174
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(186 citation statements)
references
References 68 publications
5
174
0
7
Order By: Relevance
“…These results support the potential efficacy of 5-HT 2A antagonists against PD dopaminergic psychosis demonstrated previously with ACP-103 (Meltzer et al, 2010). The data are also in accordance with two recent anatomical studies which found increased 5-HT 2A receptor levels in the temporal cortex of PD patients with visual hallucinations (Ballanger et al, 2010;Huot et al, 2010b).…”
Section: Serotonergic and Dopaminergic Transporters Inhibition And Onsupporting
confidence: 81%
“…These results support the potential efficacy of 5-HT 2A antagonists against PD dopaminergic psychosis demonstrated previously with ACP-103 (Meltzer et al, 2010). The data are also in accordance with two recent anatomical studies which found increased 5-HT 2A receptor levels in the temporal cortex of PD patients with visual hallucinations (Ballanger et al, 2010;Huot et al, 2010b).…”
Section: Serotonergic and Dopaminergic Transporters Inhibition And Onsupporting
confidence: 81%
“…Use of the selective 5-HT2A antagonist pimavanserin has been shown to resolve psychotic behavior in an animal model (6-hydroxydopamine), while in clinical trials use of pimavanserin, previously demonstrated to be well tolerated, has more recently been reported to have a beneficial effect on VH in PD patients [56][57][58].…”
Section: B)c) Serotoninmentioning
confidence: 99%
“…When assessing the eligibilities of the full-text articles, 12 articles were excluded. Five of these articles did not use the BPRS or UPDRS-III as the endpoint, [23][24][25][26][27] five were lacked necessary information, 12,[28][29][30][31] one was a study including not patients with PD, 13) and one was an extension of an open-label study of another appropriate study. 32) Therefore, ten articles were potentially appropriate for the present study.…”
Section: Resultsmentioning
confidence: 99%